Campus bullying victimization and its influencing factors among primary and middle school students in a division of Xinjiang Production and Construction Corps - Jia HE; Wei DU; Rushuang ZENG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the prevalence and associated factors of bullying victimization among primary and middle school students in a division of Xinjiang Production and Construction Corps for providing evidence to the prevention of campus bullying. MethodsUsing stratified random cluster sampling, we conducted an onsite questionnaire survey about school bullying and related factors among 3 019 primary and secondary school students in 7 urban and 5 rural schools in a division of Xinjiang Production and Construction Corps during August - October 2020. The collected data were analyzed with χ2 test and logistic regression in SPSS 20.0. ResultsOf the 3 010 students with valid response, 19.0% reported bullying victimization during past 30 days; verbal violence, emotional neglect, and physical violence were reported by 17.8%, 5.1%, and 3.9% of the students. Significantly higher overall and three types of bullying victimization were reported by boy students, day students, the students with daily sleep time of more than 8 hours, the students ever having parental maltreatments, being primary school students, and the students ever fighting with others at least two times (all P < 0.05). The results of multivariate logistic regression analysis revealed following risk factors for overall and the three types of bullying victimization: (1) being boy students and ever having parental maltreatments were risk factors for bullying victimization (odds ratio [OR] = 1.253 and OR = 2.096), verbal violence (OR = 1.339 and 2.209), and physical violence (OR = 1.964 and OR = 3.472); (2) ever fighting with others (once and ≥ twice ) was a risk factor for bullying victimization (OR = 3.184 and OR = 5.730), verbal violence (OR = 3.770 and OR = 6.974) , and emotional neglect (OR = 3.767 and OR = 6.338); (3) alcohol drinking was a risk factor for bullying victimization (OR = 1.964); (4) frequent reduction in exercise time was a risk factor for bullying victimization (OR = 1.604) and verbal violence (OR = 1.593). Further cumulative effect analysis showed that the students exposed to the 3 and more risk factors were at a significantly increased risk of bulling victimization (OR = 8.839) (P < 0.05).ConclusionBullying victimization, especially verbal violence, was prevalent among primary and secondary school students in a division of the Xinjiang Production and Construction Corps; special concern should be paid to boy students, the students ever fighting with others, having parental maltreatments and having reduction in exercise time when carrying out relevant interventions.